The association between dietary knowledge based on the Chinese Dietary Guidelines and adherence to healthy dietary habits: a large-scale cross-sectional study - Ren, Zhongyu; Hao, Zixuan; Cao, Jianhua (Frontiers in Psychology, 2024)
Introduction Previous systematic review has shown that individuals with more comprehensive dietary knowledge tend to engage in healthier eating patterns among American or European population. However, research on the association between dietary knowledge based on the Chinese Dietary Guidelines and healthy dietary behaviors, particularly among adolescents and college students in China, is lacking. This study aimed to examine the association between dietary knowledge based on the Chinese Dietary Guidelines and adherence to healthy dietary behaviors among adolescents and college students in China. Methods A cross-sectional study was conducted in China in August and October 2023. The study involved 527 adolescents and 11,856 college students. A convenience and cluster sampling methodology was employed to select one or two grades from 33 different university majors. The dietary behaviors of college students were evaluated by assessing their consumption of nine food groups: water, eggs, milk and milk products, vegetables, fruit, red meat, soy and soy products, seafood, and sugar-sweetened beverages. The dietary behaviors of adolescents were evaluated by assessing their consumption of five food groups: fast food, salty snack foods, fruits, vegetables, and soft drinks and sugared fruit beverages. The participants’ dietary knowledge was assessed using the Chinese Dietary Guidelines. The relationship between dietary knowledge and behaviors was examined using a multivariate logistic regression analysis. Results The questionnaire response rate was 100.0%. Multivariate logistic regression analysis revealed a significant positive association between dietary knowledge and the likelihood of exhibiting diverse dietary behaviors among college students. After adjusting for gender, age, family income, place of residence, and parents’ education levels, the results demonstrated a positive association between dietary knowledge and adherence to 4–8 eating habits among college students. In contrast, similar association was not observed among adolescent. Conclusion This study revealed a significant association between dietary knowledge based on the Guidelines and adherence to healthy dietary behaviors among college students in China. That is to say, the higher the level of dietary knowledge based on the Guidelines among college students, the healthier the dietary behaviors they tend to adopt in their daily lives. These findings indicate the necessity of developing educational interventions based on the Guidelines to enhance dietary knowledge among individuals with limited dietary knowledge. Such interventions could facilitate the acquisition of essential health-related knowledge and strengthen motivation to engage in healthy dietary behaviors. Future studies should employ longitudinal prospective designs or randomized controlled trials in order to establish a causal association between dietary knowledge based on the Guidelines and healthy dietary behaviors.